The Effect Of Using Social Media And Collaborative Platforms In Improving Christian Religious Education Learning Motivation In Grade XI - Sri Renata Sagala; Bangun Munthe; Imelda Butarbutar (STABN RADEN WIJAYA WONOGIRI, 2023)
The purpose of this study is to see the extent of the influence of social media and collaborative platforms in Increasing Student Learning Motivation in Christian Religious Learning Class XI SMA Negeri 2 Percut Sei Tuan with a total of 30 people. This study uses a descriptive method, while the data analysis carried out by the hypothesis research is the correlation of product moment person with the data collection tool is a questionnaire. From the test results, a correlation (r) of 0.64 was obtained with a determination test of 40.96% and to find out whether the correlation coefficient is significant or not at the real level (α) = 0.05, a